Identifikasi Air Tanah Daerah Agrotechno Park Cangar Batu Jawa Timur Berdasarkan Metode Geolistrik Resistivitas: Siti Ainur Rohmah, Sukir Maryanto, Adi Susilo - Siti Ainur Rohmah Siti Ainur Rohmah; Sukir Maryanto Sukir Maryanto; Adi Susilo Adi Susilo (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2018)
The study of groundwater has been done at Agrotecnopark Cangar using resistivity method. Data acquisition were performed by using dipole-dipole mapping configuration along 11 lines in 2 regions. Inversion method is carried out on the acquisition data using Res2dinv software. The result of inversion is distributed resistivity value in depth laterally sections. They represents subsurface structure from each line in 2D and 3D form. Based on result known in the research area dominated by high resistivity. The region 1 (AL 01 - 05) has low resisistivity in ranged 100-500 Ohm.m. which their depth arround 5 meters below ground surface. The resistivity range is suspected as the water-content layer so the layer has a low groundwater potential for region 1. While in region 2 (AL06 - AL11) has resistivity dominated by high resistivity >1000 Ohm.m. The value indicates in region 2 has no potential for groundwater.